Strategic tools in China/strategic tools: an investigation into strategy in practice in China - He, H. (2012)
In the last decades, we have been observing an increasingly dynamic and turbulent environment, where change seems to be something unavoidable and ubiquitous. This scenario of permanent instability has boosted strategy significance since its object of study is the relationship between organizations and their environment. Besides, the increased complexity agonizes the limitations of human cognition and increases bias in strategic decisions. Under this prism, companies throughout the world search for strategic practices that enable them to handle the environment volatile conditions. Therefore, strategic tools such as SWOT Analysis, Scenario Analysis or Balanced Scorecard have progressively gained importance in organizational life. Some literature also indicates that strategy tools are important to create a sense of organizational direction and to improve strategic thinking. Moreover, companies invest vast amount of resources (for example, time, money, intellectual capital) in acquiring and implementing the tools. There have not been that many studies concerning strategic tools use around the world. For a more meaningful observation of strategic tools use in a wider geographical area we have conducted a strategic tools use survey in Mainland China. The study was spread out to Beijing city, Shaanxi province and Shanxi province and 158 questionnaires were collected. From our survey, we found that SWOT analysis is the most used tool, and followed by PEST Analysis, Brain Storming and Resource Analysis. In addition, our findings in regard to large size companies show that they consider strategic tool increase the rational of the decision making and helped to clarify the strategy of the company.